THE EFFECT OF COOPERATIVE LEARNING MODELSPICTURE TYPE AND PICTUREHELPED MEDIA POSTERS TO THE RESULTS LEARNING CLASS VIII STUDENTS IN CHRISTIAN JUNIOR HIGH SCHOOL WAIBAKUL - Nefesi Rambu Woji Pekujawang; Vidriana Oktoviana Bano; Riwa Rambu Hada Enda (Universitas Labuhanbatu, 2023)
Causes some students to be often tired in class, while others become docile, lack confidence, pay less attention, and be distracted by friends. The results of students' learning are impacted by this At Waibakul Christian Middle School, grade VIII students participated in this study to find out how the Cooperative Learning Model, which uses pictures and pictures typed out by media posters, affected their learning outcomes.Â Research of this kind is experimental research. Class VIII MIPA 1 served as the control class in this study whereas VIII MIPA 3 served as the experimental class. Using a quasi-experimental research design. 49 students made up the sample for this study, which employed non-probability sampling methods, namely the purposive sampling methodology. From pre- and post-testing, learning outcomes in the cognitive domain are determined. The statistical method used for the analysis is a test paired sample t-test. The study's findings showed that the experimental class's average value was 71 and the control class's was 55. It can also be deduced that the cooperative learning model, image and picture kinds, and poster medium supported by Waibakul Christian Middle School class VIII students' learning outcomes since test paired sample t-test earned value sig (2-tailed) 0.000 0.05.Â Keywords: Cooperative, Picture and Picture, Poster Media, Learning Outcomes, Learning ModelAbstrak Menyebabkan sebagian siswa sering lelah di dalam kelas, sedangkan sebagian lainnya menjadi penurut, kurang percaya diri, kurang perhatian, dan teralihkan perhatiannya oleh teman. Hasil belajar siswa dipengaruhi oleh hal tersebut Di SMP Kristen Waibakul, siswa kelas VIII berpartisipasi dalam penelitian ini untuk mengetahui bagaimana Model Pembelajaran Cooperative yang menggunakan gambar dan gambar yang diketik dengan media poster mempengaruhi hasil belajar mereka. Jenis penelitian ini adalah penelitian eksperimen. Kelas VIII MIPA 1 sebagai kelas kontrol dalam penelitian ini sedangkan VIII MIPA 3 sebagai kelas eksperimen. Menggunakan desain penelitian eksperimen semu. Sampel penelitian ini berjumlah 49 siswa yang menggunakan metode non-probability sampling yaitu metodologi purposive sampling. Dari pra-dan pasca-tes, hasil belajar dalam domain kognitif ditentukan. Metode statistik yang digunakan untuk analisis adalah uji paired sample t-test. Hasil penelitian menunjukkan bahwa nilai rata-rata kelas eksperimen adalah 71 dan kelas kontrol adalah 55. Dapat juga disimpulkan bahwa model pembelajaran kooperatif, jenis gambar dan gambar, dan media poster didukung oleh hasil belajar siswa kelas VIII SMP Kristen Waibakul. karena uji paired sample t-test diperoleh nilai sig (2-tailed) 0,000 0,05.